Chinese Women in Leadership - Ke, Jie.; McLean, Gary N. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This edited collection highlights the unique cultural and socioeconomic elements of China and the strong influence of those elements on women leaders in the nation. The authors present perspectives on women leaders' current state of working conditions and balancing of personal and professional lives in diverse contexts while discussing commonalities and differences across sectors in China and drawing comparisons with Asian and non-Asian contexts. Chapters explore cultural contexts that hinder career advancement, family roles for women, government policies and educational opportunities that support women's development, and finally the future for women in China. The book provides a thorough assessment of the situation of women in China for scholars in leadership, management, international relations, and human resource development. Jie Ke is Associate Professor of Human Resource Development in the College of Education and Human Development at Jackson State University, USA. Her research interests include Chinese HRD/management, evaluation and assessment, women's leadership development, Chinese family entrepreneurship, motivations and needs of adult undergraduates, and effectiveness of eLearning. She has recently published her study on women entrepreneurs of family businesses in China in Advances in Developing Human Resources. She serves on the Board of Directors and as Co-chairs of the International Committee and China Special Interest Group for the Academy of Human Resource Development (AHRD). Gary N. McLean (EdD, PhD hon) is professor in the PhD program in organization development (OD) at Assumption University, Bangkok, and adjunct professor in the PhD program in HROD at the National Institute for Development Administration (NIDA) in Bangkok. He is professor emeritus, human resource development, University of Minnesota, and former professor at Texas A&M University and International Islamic University, Malaysia. He is past editorof several refereed journals and served as President of AHRD and IMDA. He was President of McLean Global Consulting, a family business and has been active in OD for almost 50 years with an international focus. He received AHRD's Outstanding Book of the Year Award for both an authored OD book and a co-edited book on HRD in Vietnam. He has a lifelong interest in gender research.
Chapter 1. Overview: Why are We Focusing on Developing Women Leaders in China? (Jie Ke, Judy Yi Sun) -- Chapter 2. Family Roles and Social Status (Judy Yi Sun, Jane Yuting Zhuang) -- Chapter 3. Cultural Constraints and Opportunities (Jackie Jinfang Liu) -- Chapter 4. Policies and Legislation (Jia Wang) -- Chapter 5. Educational Opportunities (Xiaoping Tong, Anne Namatsi Lutomia) -- Chapter 6. Women Leaders in the Education Sector (Ying Feng, Bo Fang) -- Chapter 7. Women Entrepreneurs in the Business Sector (Kai-Wen Hsieh, Lian-juan Wang) -- Chapter 8 Women's Participation in the Government Sector (Taylor Jiang Tian, Jessica Li) -- Chapter 9. Women Leaders in the Non-Governmental Organization (NGO) Sector (Yuanlu Niu, Cynthia Sims) -- Chapter 10. China in an Asian Context (Xue Yang Coleman, Jessica Li) -- Chapter 11. China in a Non-Asian Context (Jie Ke, Millard J. Bingham) -- Chapter 12. Butterflies Emerging: Women's Leadership in China (Gary N. McLean).
Keywords: International business enterprises; Personnel management; Management; Feminism; Feminist theory; International Business; Human Resource Management; Management; Feminism and Feminist Theory